Thực trạng và giải pháp tổ chức quản lý và khai thác nguồn tài liệu nội sinh tại Trung tâm Thông tin Thư viện, Trường Đại học Kiến Trúc Hà Nội - Phạm, Thanh Bình (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
For universities, endogenous documents play a very important role in the training, researching and technology transferring of each university. The endogenous documents are increasing in number, variety of types and subjects, that’s all depending on the training scale, training majors as well as forms of training of the university. Organizing the management and exploitation of this resources are currently a problem posed to universities. In this article, the author analyze the current state and propose a number of solutions to collect, manage and exploit endogenous documents at the Hanoi Architectural University.